The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1007/bf02723152
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous immunoglobulins in severe Guillian-Barre syndrome in childhood

Abstract: The authors concur with previously published reports, that early use of IVIG could reduce the mortality and the need for intubation and mechanical ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…387 Several other studies that have compared IVIG to supportive measures or PE in children 388 and adults 389,390 showed similar findings, but patients were not always randomized, and investigators were not blinded to the treatments. [391][392][393][394][395] A systematic review of data from randomized trials revealed no significant differences in any of the outcome measures between IVIG and PE. None of the treatments significantly reduced mortality.…”
Section: Demyelinating Peripheral Neuropathiesmentioning
confidence: 99%
“…387 Several other studies that have compared IVIG to supportive measures or PE in children 388 and adults 389,390 showed similar findings, but patients were not always randomized, and investigators were not blinded to the treatments. [391][392][393][394][395] A systematic review of data from randomized trials revealed no significant differences in any of the outcome measures between IVIG and PE. None of the treatments significantly reduced mortality.…”
Section: Demyelinating Peripheral Neuropathiesmentioning
confidence: 99%
“…151 Several other studies that have compared IGIV with supportive measures or PE in children 152 or adults 153,154 showed similar findings, but patients were not always randomized, and investigators were not blinded to the treatments. [155][156][157][158][159] IGIV is thus considered equivalent to PE in the treatment of GBS but is used more frequently because of reduced availability of PE, vascular access, and safety issues, particularly in children or patients with autonomic instability.…”
Section: Igiv In Neurologic Disordersmentioning
confidence: 99%
“…There was no change in median duration of ventilation, and a borderline reduction in median days to walk . Results for smaller series were grouped . Seven series ( n =96) including 83 treated with IVIG found complete or substantial improvement in motor function in 82% ( n =68).…”
Section: Resultsmentioning
confidence: 99%
“…16 Results for smaller series were grouped. [17][18][19][20][21][22][23] Seven series (n=96) including 83 treated with IVIG found complete or substantial improvement in motor function in 82% (n=68). These studies were heterogeneous, and included patients with features of Miller Fisher syndrome, 20 acute disseminated encephalomyelitis (ADEM), 19 and after immunoablation.…”
Section: Peripheral Nervous System Indications Guillain-barr E Syndromementioning
confidence: 99%